Proceedings of the first Workshop on Bio-Medical Semantic Indexing and Question Answering, a Post-Conference Workshop of Conference and Labs of the Evaluation Forum 2013 (CLEF 2013) , Valencia, Spain, September 27th, 2013

Fair Bandwidth Sharing among Virtual Machines in a Multi-criticality Scope - Grösbrink, Stefan; Almeida, Luis; de Sousa, Mario; Petters, Stefan M. (5th Workshop on Adaptive and Reconfigurable Embedded Systems (CPSWeek 2013))

Accelerating Online Model Checking - Qanadilo, Mona; Samara, Sufyan; Zhao, Yuhong (6'th Latin-American Symposium on Dependable Computing (LADC 2013))

Bildangereicherte Kartenerstellung zur Unterstützung bei Rettungseinsätzen - Stern, Claudius; Rasche, Christoph; Kleinjohann, Lisa; Kleinjohann, Bernd (11. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung)

Statistisches Planen in einem realen Roboterszenario - Rasche, Christoph; Bieshaar, Maarten; Jungmann, Alexander; Kleinjohann, Lisa; Kleinjohann, Bernd (Entwurf mechatronischer Systeme, Verlagsschriftenreihe des Heinz Nixdorf Instituts, Paderborn, Band 310)

Architecture for Adaptive Resource Assignment to Virtualized Mixed-Criticality Real-Time Systems - Grösbrink, Stefan; Baldin, Daniel; Oberthür, Simon (ACM SIGBED Review, Band 10)

SystemC Verification Components - An enhanced OVM/UVM for SystemC - Kuznik, Christoph; F. S. Oliveira, Marcio; Müller, Wolfgang (edaWorkshop 13)

Funktionale Verifikation von Low-Power Designs unter Verwendung Virtueller Prototypen - Mischkalla, Fabian; Müller, Wolfgang (Methoden und Beschreibungssprachen zur Modellierung und Verifikation von Schaltungen und Systemen (MBMV))

SC OVM: An Advanced SystemC Library for OVM-based Verification - Kuznik, Christoph; F. S. Oliveira, Marcio; Müller, Wolfgang (Open SANITAS SystemC Verification Workshop)

Informationstechnik spart Ressourcen - Engels, Gregor; Gerth, Christian; Kleinjohann, Lisa; Kleinjohann, Bernd; Müller, Wolfgang (ForschungsForum Paderborn)

Basics of Virtual Machine Migration on Heterogeneous Architectures for Self-optimizing Mechatronic Systems - Necessary Conditions and Implementation Issues - Grösbrink, Stefan (Production Engineering Research & Development 7(1))

Learning Service Recommendations - Jungmann, Alexander; Kleinjohann, Bernd; Kleinjohann, Lisa (International Journal of Business Process Integration and Management 6(4))
The as a service paradigm reflects the fundamental idea of providing basic coherent functionality in terms of components that can be utilised on demand. These so-called services may also be interconnected in order to provide more complex functionality. Automation of this service composition process is indeed a formidable challenge. In our work, we are addressing this challenge by decomposing service composition into sequential decision making steps. Each step is supported by a recommendation mechanism. If composition requests recur over time and if evaluations of composition results are fed back, a proper recommendation strategy can evolve over time through learning from experience. In this paper, we describe our approach of modelling this service composition and recommendation process as Markov decision process and of solving it by means of reinforcement learning. A case study serves as proof of concept.

Systematic Application of UCIS to Improve the Automation on Verification Closure - Kuznik, Christoph; Oliveira, Marcio F.; Defo, Bertrand; Müller, Wolfgang (Proceedings of DVCON)

A 3D Path Planning Approach Extended by Bifurcation Theory for Formation Flights - Rasche, Christoph; Stern, Claudius; Kleinjohann, Lisa; Kleinjohann, Bernd (Recent Advances in Robotics and Automation, Studies in Computational Intelligence, Band 480)
After big disasters, search and rescue missions take place. During these missions it is essential to obtain an overview of the overall situation to arrange efficient rescue tasks as soon as possible. Afterwards, this information has to be continuously updated during the complete mission in order to quickly respond to changing conditions. The use of unmanned aerial vehicles (UAVs) is a viable choice to obtain such an overview in a fast and efficient way. Using multiple UAVs, the problem of coordination has to be solved to decrease the time needed to explore an area. We present an approach for the coordination of UAVs by setting up formation patterns using bifurcation theory. We combine this theory with a potential field approach for exploration, based on harmonic functions.

Fault-Tolerant Deployment of Real-Time Software in AUTOSAR ECU Networks - Klobedanz, Kay; Jatzkowski, Jan; Rettberg, Achim; Müller, Wolfgang (International Embedded Systems Symposium (IESS) 2013)

Die wissenschaftliche Begleitung des Modellprojektes - Büker, Petra; Bührmann, Thorsten; Kordulla, Agnes (Hand in Hand durch den Übergang - Neue Wege der Kooperation zwischen Kita und Grundschule im Modellprojekt Kinderbildungshaus Paderborn)

Individualisierung, Integration, Inklusion: KiTas und Grundschulen auf dem Weg - Büker, Petra (DDS (Zeitschrift der Gewerkschaft Erziehung und Wissenschaft, Landesverband Bayern), H. 7/8, Themenheft: Frühkindliche Bildung)

Forschung und Praxis im Dialog?! Erfahrungen und Probleme der wissenschaftlichen Begleitung von Projekten im Übergang Kita-Grundschule. Keynote an der 18. Jahrestagung des Nordverbunds Schulbegleitforschung, Universität Osnabrück - Büker, Petra; Bührmann, Thorsten
September 2013

Individualisierung, Integration, Inklusion: Kitas und (Grund-) Schulen auf dem Weg. Abschlussvortrag im Rahmen des Fachtages des GEW Bezirksverbandes Oberbayern zum Thema "Individuelle Förderung als Grundlage der Inklusion". GEW Bezirksverband Oberbayern, Freising - Büker, Petra
April 2013

Verzahnung von Elementar- und Primarbereich in Bildungshäusern: Auswirkungen auf Kinder, Erzieher/innen und Lehrkräfte. Symposium an der 1. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF) an der Christian-Albrecht-Universität Kiel - Büker, Petra; Arndt, Petra A.
März 2013